Experimental and Numerical Analysis of a Novel Display Case Design: Case Study of the Renovated Anne Frank House. (3rd July 2020) - Kompatscher, Karin; Ankersmit, Bart; Neuhaus, Edgar; van Aarle, Marcel A.P.; van Schijndel, Jos W.M.; Schellen, Henk L.
ABSTRACT: Many museums are housed in historic buildings, sometimes the building itself is part of the museum collection. Creating a stable environment by providing a nearly constant temperature and relative humidity at correct levels decreases the risk of object degradation. Maintaining this steady indoor environment, however, increases energy consumption and risks to the historic building. Museum display cases offer a solution to the mitigation of risks to which valuable objects may be subjected by providing an extra layer of protection to indoor climate fluctuations. The Anne Frank House is a historic house museum located in Amsterdam. The museum has undergone several renovations in the last years to deal with an increase in the number of visitors to over 1.2 million a year. The original diaries and other documents of Anne Frank are permanently on display in the Anne Frank House. With the recent refurbishment the possibility arose to design a new state-of-the-art display case. This study presents the results of the experimental research related to the design, performed in-situ. The temperature and relative humidity in the new exhibition space and inside the new display cases were monitored to gain insight into the hygrothermal behavior of these controlled environments. A complementary numerical study was performed to investigate effects of dynamic climate control of the exhibition gallery and climate conditions in the display case under various circumstances. Four main conclusions are presented in this paper. The investigated display case design is able to provide a stable relative humidity environment by means of silica gel, while using an active box-in-box climate control system to create stable temperature conditions. The inner case temperature depends on the temperature supplied by the display case air handling unit. Protocols must be in place in case of malfunction or failure of the climate control system of the display case. The air handling unit of the case needs to be shut off to create a passive environment for the objects on display until necessary actions are taken. Exhibition gallery set points can be less stringent when susceptible museum objects are on display in the display case. The environments are separated and provide an opportunity for energy saving set point strategies. The last conclusion drawn is that the numerical study provides valuable insight into imposing dynamic control of set points for temperature and relative humidity in the exhibition gallery and the effect on the display case environment.